Quality Of Life Male Prisoners Based on Age and Education: Preliminary Studies - Prystia Riana Putri; Megah Andriany; Artika Nurrahima (Poltekkes Kemenkes Jakarta III, 2020)
Prisoners in the correctional area are faced with unexpected situations and conditions. Prisoners ability to solve problems will affect the level of quality of life (QOL). However, research that focused on QOL levels based on age and education is not yet available, so this research is essential. This study applied a cross-sectional design with systemic random sampling and purposive sampling techniques. QoL measurements were carried out at 120 male prisoners using WHOQOL BREF instruments that have been tested as valid and reliable. The study was conducted in one of the Prisons in Central Java Province in September 2019. Inclusion criteria were no family visits, occupation of prisons for less than 18 months, general crime, and no cognitive impairment. The results showed that male prisoners with late adulthood and high school education had higher QOL mean rates of 88.5 and 87.6. The conclusion is the level of QOL related to age and high education.